(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Mrs. Anitha K, Assistant Professor, Dept. of Pharmaceutical Chemistry, Dr M.G.R Educational and Research Institute, Vellappanchavadi, Chennai, Tamil Nadu, India Abstract Musculoskeletal disorder management requires distinct algorithms that differentiate between inflammatory, degenerative, metabolic, and crystal-driven pathologies. The algorithm for Rheumatoid Arthritis (RA) is a proactive "treat-to-target" strategy, initiating disease-modifying antirheumatic drugs (DMARDs), primarily methotrexate, immediately upon diagnosis. Failure to achieve low disease activity within 3-6 months triggers a stepwise escalation to combination DMARDs, biologic agents (e.g., TNF-inhibitors), or JAK inhibitors. In contrast, the algorithm for Osteoarthritis (OA) is a stepwise, symptom-focused approach beginning with non-pharmacological interventions like weight loss and physical therapy. The algorithm then progresses through analgesics, from topical and oral NSAIDs to intra-articular injections, culminating in surgical arthroplasty for refractory cases. The algorithm for Osteoporosis is one of risk prevention, using FRAX and DXA scores to identify high-risk individuals. First-line therapy is an antiresorptive agent, typically an oral bisphosphonate, with anabolic agents reserved for very high-risk patients. Gout management is bifurcated: acute attacks are treated with anti-inflammatories (NSAIDs, colchicine, or steroids), while the chronic algorithm involves urate-lowering therapy (e.g., allopurinol) titrated to a serum uric acid target of < 6 mg/dL. Keywords: Musculoskeletal Algorithms, Rheumatoid Arthritis, Osteoarthritis, Osteoporosis, Gout, Treat-to-Target VIEW PDF